2003
DOI: 10.1093/jxb/erg223
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among shoot sinks for resources exported from nodal roots regulate branch development of distal non‐rooted portions of Trifolium repens L.

Abstract: Two manipulative experiments tested hypotheses pertaining to the correlative control exerted by nodal roots on branch development of the distal non-rooted portion of Trifolium repens growing clonally under near-optimal conditions. The two experiments, differing in their pattern of excision to manipulate the number of branches formed at the first 9-10 phytomers distal to the youngest nodal root, each found that after 20 phytomers of growth the total number of lateral branches formed on the primary stolon remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…This decline in primary stem apical bud activity occurred ahead of a similar decline in growth of the basalmost lateral branches (Fig. 4) and might be related to the interaction between lateral branches and the primary stem apical bud we described previously (Thomas et al 2003b). Similar declines in primary stem apical bud activity occurred in Tradescantia grown with basal roots in small as compared with large pots, but not until the bud had produced at least 19 phytomers (Thomas and Hay 2009).…”
Section: Basal Root Vigoursupporting
confidence: 78%
See 1 more Smart Citation
“…This decline in primary stem apical bud activity occurred ahead of a similar decline in growth of the basalmost lateral branches (Fig. 4) and might be related to the interaction between lateral branches and the primary stem apical bud we described previously (Thomas et al 2003b). Similar declines in primary stem apical bud activity occurred in Tradescantia grown with basal roots in small as compared with large pots, but not until the bud had produced at least 19 phytomers (Thomas and Hay 2009).…”
Section: Basal Root Vigoursupporting
confidence: 78%
“…The species of Calystegia and Tradescantia reproduce almost exclusively by asexual means in New Zealand (Roy et al 1998) and, as in our previous studies, the Trifolium plants were derived from a stock clone of a single genotype selected from a Spanish ecotype collection (AgResearch Accession no. C1067) as previously described (Thomas et al 2002(Thomas et al , 2003bHay 2007, 2008a). Stock plants of the specific genotype of each species were maintained in the greenhouse from which experimental cuttings were taken.…”
Section: Study Speciesmentioning
confidence: 99%
“…exploitation of the resources of a niche. Our observation that RSR regulates both axillary bud outgrowth and stem elongation in T. repens (Thomas et al, 2003b) suggests it is likely that these inter-specific differences are mediated by differences in RSR supply and/or allocation.…”
Section: Discussionmentioning
confidence: 88%
“…Under these circumstances, following an initial phase in which axillary buds grow out vigorously into branches, a very predictable restriction in the branching pattern develops in all ten species that have been examined (Lötscher and Nösberger, 1996; Thomas et al ,2002, 2003a; Thomas and Hay, 2004, 2008 b , 2010), as shown for Trifolium repens L. (white clover) in Fig. 1.…”
Section: Introductionmentioning
confidence: 91%
“…The pattern of branching decline at successively formed unrooted nodes then repeats precisely that occurring in response to the basal root system (Thomas et al , 2002). Using T. repens as an exemplar for this group, our work has shown that this stimulatory influence of roots is the dominant factor involved in the regulation of axillary bud outgrowth into branches (Thomas et al , 2002, 2003 a , b ; Thomas and Hay, 2007, 2008 a , 2009). In the erect-stemmed model plant systems described above, however, it has clearly been demonstrated that there is a network of shoot and root feedback and interacting signals that collectively operate to regulate branching (Beveridge, 2006; Aguilar-Martínez et al , 2007; Simons et al , 2007; Ongaro and Leyser, 2008; Ferguson and Beveridge, 2009; Shimizu-Sato et al , 2009; Dun et al , 2009 a , b ; Leyser, 2009; Domagalska and Leyser, 2011).…”
Section: Introductionmentioning
confidence: 99%